Arabic education in Nigerian universities: the university of Ibadan as a model (2023)
This research aimed to shed light on the reality of Arabic education in Nigerian universities, with a special focus on what distinguishes the Department of Arabic Language and Islamic Studies at the University of Ibadan, which is considered the oldest scientific facility in this land. This excavation was carried out by investigating the stages through which Arabic activities passed through, and it explained its educational trends, which are not adopted by other Nigerian universities, especially with regard to teaching foreign languages. While the University of Ibadan was a British product, the establishment of subsequent universities was up to the Nigerian government. The research adopted the historical and inductive approach and concluded that the Nigerian universities that conduct Arabic programmes responded in their Arabic education to purely Arab trends, while the educational policy of the University of Ibadan was rooted in the ideologies of the colonialists since the dawn of its inception and continues despite the introduction of multiple developments to the university and its systems. This situation cannot be changed except by amending the university's educational policy left behind by the British colonization of the country and upon which the university was founded.